2019
DOI: 10.1142/s1793545819400054
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission luminogen for in vivo three-photon fluorescence lifetime microscopic imaging

Abstract: Compared with visible light, near-infrared (NIR) light has deeper penetration in biological tissues. Three-photon fluorescence microscopy (3PFM) can effectively utilize the NIR excitation to obtain high-contrast images in the deep tissue. However, the weak three-photon fluorescence signals may be not well presented in the traditional fluorescence intensity imaging mode. Fluorescence lifetime of certain probes is insensitive to the intensity of the excitation laser. Moreover, fluorescence lifetime imaging micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Due to the much reduced scattering and absorption, 3PA at these wavelengths is limited only by signalto-noise ratio (which depends on protein brightness) up to more than 3 mm depth (Horton et al, 2013), and structural imaging of neurons has already been demonstrated at a depth of 1.4 mm (Horton et al, 2013), reaching the subcortical region of the mouse brain. Especially if combined with FLIM detection (Ni et al, 2019), that eliminates artifacts due to absorption and scattering, 3PA at 1700 nm would constitute a promising strategy for non-invasive imaging of neurochemicals in deep brain regions, while at the same time improving the cell resolution ability in densely labeled samples with respect to two-photon absorption (Ouzounov et al, 2017). and of their spectroscopic properties (right).…”
Section: The Push Toward Red-shifted Wavelengthsmentioning
confidence: 99%
“…Due to the much reduced scattering and absorption, 3PA at these wavelengths is limited only by signalto-noise ratio (which depends on protein brightness) up to more than 3 mm depth (Horton et al, 2013), and structural imaging of neurons has already been demonstrated at a depth of 1.4 mm (Horton et al, 2013), reaching the subcortical region of the mouse brain. Especially if combined with FLIM detection (Ni et al, 2019), that eliminates artifacts due to absorption and scattering, 3PA at 1700 nm would constitute a promising strategy for non-invasive imaging of neurochemicals in deep brain regions, while at the same time improving the cell resolution ability in densely labeled samples with respect to two-photon absorption (Ouzounov et al, 2017). and of their spectroscopic properties (right).…”
Section: The Push Toward Red-shifted Wavelengthsmentioning
confidence: 99%
“…[9][10][11][12][13] To further increase the achievable imaging depth, three-photon fluorescence microscopy (3PM) has been explored and developed in the past. [14][15][16] 3PM uses NIR-II (900-1700 nm) excitation light, 17,18 which leads to reduced scattering and overall attenuation and thus to increased penetration depth in tissue. Furthermore, the fluorescence of three-photon excitation falls off as B1/z 4 (where z is the distance from the focal plane), which yields less out-of-focus background and therefore a better signal-tobackground ratio (SBR) at significant tissue depths.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The ACQ effect not only limits the brightness of such molecules for biological imaging, but also restricts their photostability, because organic fluorophores in isolated state at a molecular level are more easily photobleached under laser excitation, 25,26 especially at the ultrahigh pulse-energy femtosecond (fs) laser excitation which is typically used in 3PM. [14][15][16][17][18][19] In contrast to the ACQ effect, an aggregation-induced emission (AIE) phenomenon can lead to high fluorescence in the aggregate or solid state, [27][28][29] and has been widely used in various fields of biological imaging, optical guided surgery and light-induced therapy. [30][31][32][33][34] This phenomenon exists in propeller-shaped organic molecules which are non-emissive or provide weak fluorescence in benign solvents, but provide higher orders-of-magnitude fluorescence in an aggregated form.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] To further increase the achievable imaging depth, three-photon fluorescence microscopy (3PM) has been explored and developed in the past. [14][15][16] 3PM uses NIR-II (900-1700 nm) excitation light, 17,18 which leads to reduced scattering and overall attenuation and thus to increased penetration depth in tissue. Furthermore, the fluorescence of three-photon excitation falls off as∼1/z 4 (where z is the distance from the focal plane), which yields less out-of-focus background and therefore better signal-to-background ratio (SBR) at significant tissue depths.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 The ACQ effect not only limits the brightness of such molecules for biological imaging, but also restrict their photostability, because organic fluorophores in isolated state at molecular level are more easily photobleached under laser excitation, 25,26 especially at the ultra-high pulse-energy femtosecond (fs) laser excitation which is typically used in 3PM. [14][15][16][17][18][19] In contrary to the ACQ effect, aggregation-induced emission (AIE) phenomenon can lead to high amounts of fluorescence in the aggregate or solid state. [27][28][29] This phenomenon exists in propeller shaped organic molecules which are non-emissive or provide weak fluorescence in benign solvents, but provide orders-of-magnitude higher fluorescence in aggregated form.…”
Section: Introductionmentioning
confidence: 99%